2022
DOI: 10.3390/ijms23126782
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trichoderma asperellum on Wheat Plants’ Biochemical and Molecular Responses, and Yield under Different Water Stress Conditions

Abstract: Eight Trichoderma strains were evaluated for their potential to protect wheat seedlings against severe (no irrigation within two weeks) water stress (WS). Considering the plant fresh weight and phenotype, T. asperellum T140, which displays 1-aminocyclopropane-1-carboxylic acid deaminase activity and which is able to produce several phytohormones, was selected. The molecular and biochemical results obtained from 4-week-old wheat seedlings linked T140 application with a downregulation in the WS-response genes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 64 publications
2
4
0
Order By: Relevance
“…Piriformospora indica inoculated into Citrus sinensis activated the antioxidant defense system of the host plants, improving their resistance during field cultivation ( Li et al, 2022 ). In this study, the inoculation of nine endophytic fungi significantly increased the activities of SOD and PAL in S. miltiorrhiza , consistent with those in wheat leaves after inoculation with Trichoderma asperellum , effectively enhancing drought resistance ( Illescas et al, 2022 ). DS8, 10, and 16 significantly improved the activities of SOD, PAL, CAT, and POD, and Pro contents; while reducing MDA contents under pot cultures.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Piriformospora indica inoculated into Citrus sinensis activated the antioxidant defense system of the host plants, improving their resistance during field cultivation ( Li et al, 2022 ). In this study, the inoculation of nine endophytic fungi significantly increased the activities of SOD and PAL in S. miltiorrhiza , consistent with those in wheat leaves after inoculation with Trichoderma asperellum , effectively enhancing drought resistance ( Illescas et al, 2022 ). DS8, 10, and 16 significantly improved the activities of SOD, PAL, CAT, and POD, and Pro contents; while reducing MDA contents under pot cultures.…”
Section: Discussionsupporting
confidence: 72%
“…Sucrose metabolism, catalyzed by the key enzymes SS and SPS; and N assimilation, catalyzed by the major enzymes NR, GS, and GOGAT, are pivotal for plant growth. Moreover, coordinating photosynthetic C assimilation and N uptake and utilization is critical to ensuring plant yield and quality ( Illescas et al, 2022 ). This study found that under sterile conditions, DS7, 8, 10, 12, and 13 enhanced SS, SPS, NR, and GS activities and showed growth-promoting effects.…”
Section: Discussionmentioning
confidence: 99%
“…has the ability to increase the availability of micronutrients, such as copper, zinc, and manganese ions, which affect crop size and plant nutrition [58,79,148]. These observations are confirmed by the studies of Illescas et al [152], which show that T. asperellum increased manganese concentration in wheat grains by 7.01 mg per kg and copper concentration by 0.51 mg per kg of grain. Azarmi et al [153] reported that the treatment of soil and tomato seeds with T. harzianum significantly increased the concentrations of calcium, magnesium, potassium, and phosphorus in the roots and shoots of the analyzed plants.…”
Section: Increasing the Availability Of Nutrientssupporting
confidence: 52%
“…Trichoderma plant interactions can not only induce resistance but also improve the resistance of plants to abiotic stress factors (salt, high temperature, UV). Treatment of cucumber seeds with T. asperellum T203 improved the plant’s salt tolerance, and the activities of Mn/Cu SOD and catalase (CAT), and significantly reduced ascorbic acid in the plant ( Illescas et al, 2022 ). Trichoderma can significantly enhance the Na + efflux from the root system of Lycium barbarum and its transport to the upper ground, ensure K + absorption and maintain the ion balance in the plant, thus reducing the damage of PSII caused by ion toxicity and oxidative stress, protecting photosynthetic pigments, maintaining the photosynthetic performance of L. barbarum under salt stress, and reducing biomass loss ( Brotman et al, 2013 ).…”
Section: Application and Mechanism Of Action Of Trichoderma...mentioning
confidence: 99%